Sleep duration and depression among adolescents: Mediation effect of collective integration - Gao, Min; Li, Xian; Lee, Chun-Yang; Ma, Honghao; Chen, Tianmu; Zhang, Shuoxun; Chiang, Yi-Chen (Frontiers in Psychology, 2022)
Adolescence is a time of dramatic physical and mental change when adolescents are extremely vulnerable to various mental health problems. Depression and poor sleep duration are increasingly common among adolescents. This study is mainly aimed to verify the important mediating role of collective integration on sleep duration and depression and examine the interrelationship between sleep duration and depression in adolescents longitudinally. The data were obtained from the Wave 1 (in 2013-2014) and Wave 2 (in 2014-2015) longitudinal surveys of China Education Panel Survey (CEPS). The analytic sample in the present study included 8,829 seventh-grade students aged about 14 years (51.50% boys and 48.50% girls). A structural equation modeling (SEM) was used to investigate parent-child/teacher factors affecting adolescent sleep duration and depression, and Monte Carlo resampling with R was employed to confirm the significance of the mediation effects of collective integration. An autoregressive cross-lagged model was employed to analyze the interrelationship between adolescent sleep duration and depression. The findings were as follows. Firstly, collective integration strongly mediated the relationships among academic self-efficacy, parental involvement, teacher praise/criticism, sleep duration, and depression. Secondly, sleep duration and depression were found to have enduring effects and have effects on each other. Thirdly, parental involvement and teacher praise were positively associated with sleep quality and negatively associated with depression. Teacher criticism was negatively associated with sleep quality and positively associated with depression. Compared with teacher praise, teacher criticism has stronger effects on youth sleep duration and depression. In conclusion, improving sleep problems and depression in adolescents as early as possible can stop the persistent and long-term consequences of these problems. Increasing teacher praise, decreasing teacher criticism, and increasing adolescents’ collective integration were effective ways to improve adolescents’ sleep duration and mediate depression.